Environmental Impact of Gas Flaring Emissions in Oil Installations Al-Wafa Oil Field at Mellitah Company: A Case Study - م. هشام أحمد الحار; م. يوسف عبد النبي الأسود; د. عبد الناصر عمر السوسي (African Journal of Advanced Pure and Applied Sciences, 2026)
Flare gases are byproducts, either associated gases produced during oil and gas separation, processing, and production operations in oil fields such as Al-Wafa oil field or return gases from manufacturing processes in production units. These gases are flared to ensure system stability, at startup, or due to emergency shutdowns, as in reduction plants, for example. Flaring gases are known to cause environmental, health, and economic damage, resulting in greenhouse gas emissions, air pollution, and the waste of valuable energy resources. This paper aims to define flare gases, quantify the amounts flared globally, and explain modern technologies for reducing flare emissions. It also outlines methods for measuring emissions and the associated environmental and economic impacts. The methodology is based on a case study conducted at Al-Wafa oil field, operated by Mellitah Oil and Gas Company, a subsidiary of the National Oil Corporation in Libya. The study employs a descriptive, statistical, mathematical, and analytical approach, collecting data and information, and calculating the quantities of flared gases burned at the Wafa field. It also calculates greenhouse gas emissions, comparing them to global measurements and internationally recognized standards adopted by several international and local bodies and agencies. The study concludes by determining the quantities and components of flared gases, as well as the rates and types of emissions resulting from flaring at Al-Wafa field. This is based on the collected data and the use of mathematical equations to calculate the total amount of carbon dioxide (CO2e) equivalent to emissions. The study reveals that the largest proportion of emissions is carbon dioxide, a primary contributor to global warming and a serious pollutant. It concludes with recommendations regarding the potential for utilizing the large and significant volume of flared gases at Al-Wafa field.